TRADISI PIDUDUK DALAM PERKAWINAN ADAT BANJAR DITINJAU DARI PERSPEKTIF HUKUM ISLAM - RIAN CHANDRA (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2020)
This research is normative or literature research, by reviewing library materials to find out how according to Islamic law about the issue of occupational tradition in Banjar traditional marriages. The results of this study indicate that the concept of the piduduk tradition is to use several dishes in marriage. The occupation tradition is believed to refuse reinforcements in order to avoid the evil spirits that interfere with the wedding ceremony. Because the community assumed that there would be dangers to befall if the residents were not carried out. And so far the implementation of the occupation tradition in marriage has been categorized as al-urf al-fasid and al-urf al-shahih. Al-urf al-fasid, because many people believe in this position to avoid evil spirits, even though believing in other than Allah is a major sin and acts of shirk. It can become al-urf al-shahih if the person carrying out the marriage does not believe that the occupation tradition is something that causes disaster. The occupation tradition can be accepted as one of the good customs and does not contradict the Koran or the hadith if its implementation in society itself is changed, namely by straightening the intention in carrying it out instead of making us idolatrous but the address is provided only as a symbol or symbol of the expected prayer. for the bride